2016
DOI: 10.1111/papr.12539
|View full text |Cite
|
Sign up to set email alerts
|

Neurostimulation for Postsurgical Analgesia: A Novel System Enabling Ultrasound‐Guided Percutaneous Peripheral Nerve Stimulation

Abstract: While neurostimulation—stimulation of the nervous system using electrical current—has been used to treat chronic pain, its use treating postsurgical pain has been limited. Here, we report on the clinical application of a novel investigational lead to provide analgesia following total knee arthroplasty. In 5 subjects, leads were inserted percutaneously using ultrasound guidance within 0.5 to 3.0 cm of the femoral and/or sciatic nerve(s). With the delivery of current, pain decreased an average of 63% at rest, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 57 publications
4
66
0
2
Order By: Relevance
“…One lead of the current investigation broke exterior to the subject where the lead met the connection block, which has not yet been reported . Previous investigations involving the same helically coiled lead used in the current study have reported a 7.5% average incidence of fracture deep to the skin during removal (none occurred in the subjects of the current study) .…”
Section: Discussionmentioning
confidence: 79%
“…One lead of the current investigation broke exterior to the subject where the lead met the connection block, which has not yet been reported . Previous investigations involving the same helically coiled lead used in the current study have reported a 7.5% average incidence of fracture deep to the skin during removal (none occurred in the subjects of the current study) .…”
Section: Discussionmentioning
confidence: 79%
“…Accordingly, the medical professional should inform the patient regarding these matters and make a notation in the patient's medical records. It should be noted that the rate of lead fracture (as determined by visual inspection of the removed lead) associated with lead removal has been reported to be 7.5% . Notably, there were no reports of infectious or neurologic complications related to the presence of lead fragments in situ , nor any reports of indwelling leads fracturing during therapy .…”
Section: Discussionmentioning
confidence: 98%
“…No serious device‐related adverse events have occurred across all studies and, for the adverse events that did occur, these required little or no medical treatment . In addition, there have been no reports of induced sensory, motor, or proprioception deficits during use of this unique means of applying PNS, thus, enabling percutaneous PNS to be utilized during physical rehabilitation (e.g., during the immediate postoperative period) and activities of daily living .…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] In 2 of these abstracts, 32,33 a total of 10 individuals were included who experienced postoperative knee pain difficult to control with oral analgesics between 6 and 97 days after surgery. Using ultrasound guidance, a femoral and/or sciatic nerve electrical lead was inserted, depending on where most of the pain originated (anterior vs posterior).…”
Section: Application To Postoperative Painmentioning
confidence: 99%